Review of the latest local treatments for uveitis. (October 2014) - Bhat, Pooja V; Goldstein, Debra A
<x xml:space="preserve">Abstract</x> There have been many recent advances in local therapeutic options for uveitis, both corticosteroid and non-corticosteroid. Long- and short-acting steroid implants are now available, with new ones being developed. There are also new locations for drug delivery (suprachoroidal space) and new non-corticosteroid options. This paper reviews the data on the currently available local treatment options, as well as those currently under investigation. The choice of local therapy depends on whether or not there is systemic inflammatory disease also requiring treatment, if the disease is unilateral or bilateral, expected disease duration, patient preference and co-existing ocular and systemic comorbidities. For chronic disease without systemic manifestations, long-term steroid releasing implants are a good option, whereas for breakthrough inflammation and cystoid macular edema, short-term intravitreal therapy, initially with corticosteroids then with alternative agents is considered.